Comparison of the Effects of Epidural Analgesia and Patient-controlled Intravenous Analgesia on Postoperative Pain Relief and Recovery After Laparoscopic Gastrectomy for Gastric Cancer. Issue 5 (October 2019) - Kikuchi, Satoru; Kuroda, Shinji; Nishizaki, Masahiko; Matsusaki, Takashi; Kuwada, Kazuya; Kimura, Yoshikazu; Kagawa, Shunsuke; Morimatsu, Hiroshi; Fujiwara, Toshiyoshi
Abstract : Purpose: Epidural analgesia (EDA) is an imperative modality for postoperative pain relief after major open abdominal surgery. However, whether EDA has benefits in laparoscopic surgery has not been clear. In this study, the effects of EDA and patient-controlled intravenous analgesia (PCIA) after laparoscopic distal gastrectomy (LDG) were compared. Methods: This was a retrospective study that included 82 patients undergoing LDG for gastric cancer. Patients received either EDA (n=67) or PCIA (n=15) for postoperative pain relief. Postoperative outcomes and analgesia-related adverse events were compared between the two modalities. Results: EDA and PCIA patients showed no differences in the incidence of complications [9 (13%) vs. 2 (13%); P =0.99] and the length of postoperative hospital stay (9.6±4.5 d vs. 9.7±4.0 d; P =0.90), although the PCIA included poorer preoperative physical status (PS) patients. The number of additional doses of analgesics was higher in the EDA than in the PCIA (1.8±2.4 vs. 0.9±1.0; P =0.01), although postoperative pain scores were similar in the 2 groups. Though the time to first passage of flatus was shorter in the EDA ( P <0.05), more EDA patients developed postoperative hypotension as an adverse event ( P <0.01). The full mobilization day and the day of oral intake tolerance were not significantly different between the 2 groups after surgery. Conclusions: After LDG, EDA may not be indispensable, while PCIA may be the optimal modality for providing safe and effective postoperative analgesia and recovery.